2019
DOI: 10.1101/612309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined behavioral and electrophysiological evidence for a direct cortical effect of prefrontal tDCS on disorders of consciousness

Abstract: Severe brain injuries can lead to long-lasting disorders of consciousness (DoC) such as vegetative state/unresponsive wakefulness syndrome (VS/UWS) or minimally conscious state (MCS). While behavioral assessment remains the gold standard to determine conscious state, EEG has proven to be a promising complementary tool to monitor the effect of new therapeutics. Encouraging results have been obtained with invasive electrical stimulation of the brain, and recent studies identified transcranial direct current stim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In Fig. 5D we showed that transitions towards states of heightened consciousness were systematically linked to perturbations located in the precuneus, temporo-parietal junction and the middle frontal cortex, regions presenting a significant overlap with the default mode network (65) and in line with electrical stimulation targets shown to improve behavioural signatures of consciousness in DoC patients (38). These regions have also been shown to robustly reflect the level of consciousness (46,55,66,67) and conscious information access in cognitive neuroscience paradigms (1).…”
Section: Discussionmentioning
confidence: 86%
“…In Fig. 5D we showed that transitions towards states of heightened consciousness were systematically linked to perturbations located in the precuneus, temporo-parietal junction and the middle frontal cortex, regions presenting a significant overlap with the default mode network (65) and in line with electrical stimulation targets shown to improve behavioural signatures of consciousness in DoC patients (38). These regions have also been shown to robustly reflect the level of consciousness (46,55,66,67) and conscious information access in cognitive neuroscience paradigms (1).…”
Section: Discussionmentioning
confidence: 86%
“…This physiological heterogeneity may also explain the inter-subject variability in response to certain treatments. As such, recent studies demonstrated a correlation between the therapeutic efficacy of transcranial direct current stimulation, and the subjects underlying brain anatomy and metabolism (Thibaut et al ., 2015, 2018; Hermann et al ., 2019). More developed neuroimaging techniques could both help to better stratify patients for therapeutic intervention, and to develop tailored treatment strategies, which are still desperately needed for these debilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Neurostimulation has specific ethical implications for patients unable to communicate pain. Clinical effects of neuromodulation in adults with DoC are promising but heterogeneous (~40% of adults in MCS and ~10% in a vs. improved signs of consciousness [ 77 , 78 , 89 , 90 , 91 , 92 ] with transcranial direct current stimulation; safety in children is still under investigation [ 93 ]). Overall, a one-size-fits-all treatment is unlikely, and we envisage that well-defined coma endotypes will receive tailored treatments in the future.…”
Section: Medical Technologies For Treatmentmentioning
confidence: 99%